Inventario de Flora de la parroquia San José de Alluriquín, provincia Santo Domingo de los Tsáchilas. - Silva Miranda, Mariela Jadira (2021)
This project is focused on carrying out an inventory of flora in the San José de Alluriquín Parish, because the parish is beginning its development in ecotourism activities, such as bird watching and extreme sports, for which it has been considered important to promote the floristic knowledge of the place. For this, a specific area was selected, which is located at kilometer 35 via Alóag-Santo Domingo on the left of the Pilatón river, having a location so close to a river and with a temperature that ranges between 27º C It is considered as a resident focus of plant biodiversity. For the development of the research project, a diagnosis of the study area was carried out, obtaining data from the geographical, social, economic and environmental axis; in order to identify the areas where the studies were carried out, of which the choice in three specific study areas that have different characteristics stands out; Agricultural area, livestock area and the last remaining of primary forest area. In the indicated areas, a wide variety of arboreal, shrub, herbaceous, fern, climbing and creeper species were found, each one with peculiarities and specific characteristics that differentiated the structure of the vegetation in each one of them. The inventory was carried out through field trips, which allowed the species to be photographed in each of the areas, for which an intensive search was carried out along the roads used in the place, thus avoiding the opening of other roads and avoiding cause an environmental impact. ; therefore, the highest number of species was recorded and the identification was carried out through digital databases, obtaining a total of 70 species, of which one is critically endangered (CR); 1 endangered (EN); 4 are vulnerable (VU); 3 are near threatened (NT); 6 are of Least Concern (LC); one with insufficient data (ID) and 54 species are not evaluated (NE) according to the UCN (Union for Conservation of Nature). The information obtained in the inventory was synthesized in order to do the design of a descriptive guide of the identified species, it has photographs of the species, common and scientific name, conservation status and details of the species. The guide indicates the floristic richness in the study area, as well as the species that must be preserved, but it is advisable to deepen the information on their use by local communities, and the study to wildlife should be extended with technical information which will allow to increase the knowledge and generate plans and programs for ecotourism development, bird watching tourism and even community tourism.